The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00705-012-1336-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of beak and feather disease virus (BFDV) in New Zealand and its implications for managing an infectious disease

Abstract: Beak and feather disease virus (BFDV) infections are often fatal to both captive and wild parrot populations. Its recent discovery in a wild population of native red-fronted parakeets has raised concerns for the conservation of native parrots, all of which are threatened or endangered. The question of a recent introduction versus a native genotype of the virus poses different conservation-management challenges, and thus, a clear understanding of the molecular phylogeny of BDFV is a crucial step towards integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 53 publications
2
55
0
2
Order By: Relevance
“…The species has been observed reusing nest hollows (Stojanovic et al, 2012) when flowering conditions are favorable. It is not surprising that PBFD infects birds through shared nest hollows, for although a degree of host specificity is seen in psittacine circoviruses, considerable host generalism is also observed in several lineages (Varsani et al, 2011;Kundu et al, 2012;Massaro et al, 2012). Furthermore, the likely prolonged environmental persistence of circovirus virions (Raidal and Cross, 1994;Yilmaz and Kaleta, 2004) provides a mechanism by which transmission can occur in otherwise ecologically disconnected species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species has been observed reusing nest hollows (Stojanovic et al, 2012) when flowering conditions are favorable. It is not surprising that PBFD infects birds through shared nest hollows, for although a degree of host specificity is seen in psittacine circoviruses, considerable host generalism is also observed in several lineages (Varsani et al, 2011;Kundu et al, 2012;Massaro et al, 2012). Furthermore, the likely prolonged environmental persistence of circovirus virions (Raidal and Cross, 1994;Yilmaz and Kaleta, 2004) provides a mechanism by which transmission can occur in otherwise ecologically disconnected species.…”
Section: Discussionmentioning
confidence: 99%
“…Like RNA and other ssDNA viruses, BFDV is prone to a high rate of genetic mutation, although the Rep gene is relatively conserved, which conveniently assists with diagnosing infection by PCR detection methods (Ypelaar et al, 1999). Within Psittaciformes, BFDV exhibits quasispecies characteristics with emerging geographic or host specificity demonstrable within various clades (Varsani et al, 2011) and the observed occurrence of closely related clades in highly divergent parrot species is evidence of host switching or host generalism in several BFDV lineages (Varsani et al, 2011;Julian et al, 2012;Kundu et al, 2012;Massaro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. S1 shows that P. elegans BFDV isolates branch out from all other Australian endemic species and that they show a common ancestor with BFDV isolates from Platycercus eximius that were introduced into New Zealand (35). One exception is the presence of a BFDV isolated from Calyptorhynchus lathami, an endangered species that was in captivity.…”
Section: Significancementioning
confidence: 99%
“…In addition to mortality generated directly and indirectly by human activities (Lewison et al 2004;Le Bohec et al 2008), several disease outbreaks are potentially threatening many species (Rolland et al 2009;Descamps et al 2012;Massaro et al 2012). Long-lived organisms are characterized by delayed maturities, low reproductive rates, and high adult survival.…”
Section: Introductionmentioning
confidence: 99%